Improving Treatment Trial Outcomes for Rett Syndrome: The Development of Rett-specific Anchors for the Clinical Global Impression Scale. (November 2015) - Neul, Jeffrey L.; Glaze, Daniel G.; Percy, Alan K.; Feyma, Tim; Beisang, Arthur; Dinh, Thuy; Suter, Bernhard; Anagnostou, Evdokia; Snape, Mike; Horrigan, Joseph; Jones, Nancy E.
Rett syndrome is a genetically based neurodevelopmental disorder. Although the clinical consequences of Rett syndrome are profound and lifelong, currently no approved drug treatments are available specifically targeted to Rett symptoms. High quality outcome measures, specific to the core symptoms of a disorder are a critical component of well-designed clinical trials for individuals with neurodevelopmental disorders. The Clinical Global Impression Scale is a measure of global clinical change with strong face validity that has been widely used as an outcome measure in clinical trials of central nervous system disorders. Despite its favorable assay sensitivity in clinical trials, as a global measure, the Clinical Global Impression Scale is not specific to the signs and symptoms of the disorder under study. Development of key anchors for the scale, specific to the disorder being assessed, holds promise for enhancing the validity and reliability of the measure for disorders such as Rett syndrome.